Radically universal and differentialist. For a critical geography from Latin America - Herrera, Tania (2019)
This essay proposes an insight on what implies the critical analysis of reality for geography and socialsciences. Such critical view requires considering the universality of capitalism and the multiscaleinterests that produce space. Likewise, it is important to consider subjectivity and everything that goesbeyond the concept of class. In this sense, it is necessary to point out the shadow left by a perniciousattitude of researchers identified with postcolonial theory, who seek to understand the Latin Americanterritories under local conceptual referents, an arrange of words locally created. If something can berescued from these ideas, that is the implicit denunciation to the powers that dictate the norms ofproduction and circulation of knowledge, intimately linked to global geopolitical interests. Thus, theessay proposes a journey through the genesis of critical, anti-imperialist and militant geography. Next,a dialogue is proposed between two great authors of the 20th century, Henri Lefebvre and José MaríaArguedas; of Lefebvre we take the concept of difference and exemplify this concept through a storywritten by Arguedas in “Los Ríos Profundos”. The objective with this dialogue is to provoke reactionsto those who insist that Latin America and its territories cannot be understood through categoriescreated outside the continental limits.